Human` Complexity and Man`s Atrocity: Causes Of Medical Malpractices among Pakhtuns of Pakistan - Naz, Arab; Daraz, Umar; Khan, Waseem; Khan, Qaisar; Khan, Tariq; Alam, Anwar; Mughal, Irum (Asian Journal of Empirical Research, 2013)
This study investigates various socio-economic causes of medical malpractices among Pakhtuns of District Swat Khyber Pakhtunkhwa Pakistan. A comprehensive survey was conducted in Saidu Group of teaching hospitals Mingora and data was collected through structured questionnaire from 115 educated respondents through stratified random sampling with proportional-allocation method including patients, nurses, and paramedical staff. A triangulated (Qualitative and Quantitative) approach was adopted to record the responses of the respondents’ perceptions regarding medical malpractices. The study reveals that various socio-economic causes contribute to the malpractices such as lack of health-education, untrained practitioners, un-sterilized procedures, lust for money, corruption and, vested interest groups. The study recommends that proper health education; awareness among people, proper health policy, ban on quackery and deterrence to drug black marketing will help reduce and eliminate medical practices.